The Legal Protection for Parties in Electronic Purchase Agreements with Cash on Delivery System - Ramadhan, Syaiful Nur Aditya; Bawono, Bambang Tri (Jurnal Konstatering, 2023)
This study aims to find out and analyze the legal position of electronic sales agreements with the cash on delivery system, as well as legal protection for the parties in electronic sales agreements with the cash on delivery system. This study uses a normative juridical approach that is analytical descriptive. The data used is secondary data, which is then analyzed qualitatively. Based on the research, it was concluded that: (1) the legal position of the electronic sale-purchase agreement with the cash on delivery system is valid as an agreement that fulfills the legal requirements according to the provisions of Article 1320 of the Civil Code and Article 46 of Government Regulation Number 71 of 2019, so that an agreement that creates a legal relationship that results in the emergence of rights and obligations for the parties; (2) legal protection for the parties to electronic buying and selling agreements with a cash on delivery system, both for sellers (merchants), buyers and expediting services (courier) in a preventive manner by forcing the implementation of obligations as stipulated in the Civil Code, Act No. 8 of 1999, Act No. 11 of 2008 jo. Act No. 19 of 2016, Government Regulation Number 71 of 2019, Government Regulation Number 80 of 2019, as well as in the Criminal Code, while in a repressive manner it is carried out by filing a claim from the aggrieved party through litigation or non-litigation. Keywords: Buy; Protection; Sell.